Potensi Kombinasi Ekstrak Daun Matoa (Pometia pinnata) dan Ektrak Daun Kelor (Moringa oleifera) sebagai Antidiabetik Pada Mencit (Mus musculus) Terinduksi Alloksan - Siti Haryani Muayadah; Aceng Ruyani; Afrizal Mayub; Bhakti Karyadi; Rendy Wikrama Wardana (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease whose prevalence continues to increase globally. Plant-based alternative therapy is becoming an increasingly popular option due to its minimal side effects. This study aims to test the potential of a combination of matoa (Pometia pinnata) and Moringa (Moringa oleifera) leaf extracts as an antidiabetic in alloxan-induced male mice (Mus musculus). The study was conducted experimentally with five treatment groups, including negative control, positive control, and three groups of extract combination doses (100, 225, and 300 mg/kg BB). Phytochemical tests showed the content of active compounds alkaloids, flavonoids, and steroids in the combination of extracts. Blood glucose level test results showed that the combination dose of 300 mg/kg BB (Dose III) was able to reduce blood glucose levels significantly and had comparable effectiveness with glibenclamide as a standard drug. Statistical analysis (One Way ANOVA and Post Hoc Bonferroni) confirmed that Dose III showed a significant difference compared to the lower dose, and was not significantly different from the positive control.Beyond these results, this study contributes new insights by highlighting the synergistic effect of combining two medicinal plants, providing a scientific basis for the development of standardized herbal formulations as potential alternatives in diabetes management.